Development of the contact layer and its role in the phase change process. (February 2016) - Weigand, B.; Lipnicki, Z.
Highlights: The contact layer in the phase change process is very important. The thermal resistance of the gap depends on the Knudsen number. The development of the gap depending on the thickness of the solid layer. Abstract: The paper presents a simplified theoretical analysis of liquid solidification on cold flat and cylindrical walls with special emphasis on the role of the contact layer that forms on them. The theory is based on analytical calculations adapted from the kinetic theory of gases. The results show the dependence of the thickness of the contact layer on the thickness of the solidified layer. In addition, the influence of the contact layer on the solidification process has been shown. The development of the thickness of the solidified layer and the influence of the contact layer has been determined for selected liquid and solidification parameters.